Adopting a Strategy for Enhancing Generic Skills in Engineering Education. (June 2014) - Krassadaki, Evangelia; Lakiotaki, Kleanthi; Matsatsinis, Nikolaos F.
It is remarkable how often academic staff discover students' weaknesses in expressing their thoughts in written and oral contexts, and in team working. To examine these weaknesses, a study was conducted in 2009–2010 and 2010–2011 of students taking an engineering course. Students self-reported an initial high level of weakness in both communication skills (writing and speaking), while expressing higher levels of confidence in their team working skills. This suggested that there was significant potential for improvement in both forms of communication skills and a lower potential for the improvement of team-working skills. On that basis the Technical University of Crete organized short training workshops based on experiential learning methods, during the academic year 2012–13. Other factors taken into account were the lack of awareness of such skills in traditionally-organized Greek universities; the inability to redesign all courses, currently dependent on a content-based curriculum, on a competency basis; and findings in the international literature, which highlight specific generic skills of engineering students as essential to their studies and future career prospects. The aim was to enhance the three skills of writing, speaking and team working. Participation was voluntary and open to students from all schools in the university. This paper assesses this initiative and analyses the contribution of the workshops to skills development.